Personal Financial Management and Entrepreneurial Competencies among Selected Public School Teachers in Cebu City Division - Polinar, Mark Anthony; Cabatingan, Albim; Delantar, Alexander Franco (JPAIR Institutional Research, 2022)
Public school teachers are role models who mold students into better citizens, and teachers are regarded as the epitome of education and career success. Delivering financial education will be the pinnacle of absurdity if teachers do not practice personal financial management. This study investigated public school teachers’ knowledge and practice of personal financial management and entrepreneurial competencies. The study employed the descriptive-correlational method, administered to 229 selected teachers in the Cebu City Division. The main instrument, which consists of three components, was adopted and modified. The data were collected, arranged, tabulated, and interpreted using a statistical technique like weighted mean and Pearson r Product Moment Correlation Coefficient. The study revealed that public school teachers were moderately knowledgeable and practiced personal financial management. Also, they moderately manifested all the entrepreneurial competencies identified in the study. Using the Pearson Correlation Coefficient, the level of knowledge and practice of personal financial management are significantly correlated. As a result, it was concluded that public school teachers need to enhance their knowledge and practice of personal financial management, especially knowledge and practice of investing, and the other areas of entrepreneurial competencies uncovered as weak. Subsequently, the principal researcher crafted a comprehensive action plan to help public school teachers enrich their knowledge and practice of personal financial management and entrepreneurial competencies, scaffolding their financial resilience and gently nudging them to entrepreneurial ventures.